Attitudes toward palliative care among cancer patients: a multi-method study - Meiying Zhang; Yuxia Zhao; Yifu Lu; Mengyun Peng (Frontiers in Public Health)
BackgroundPalliative care plays a crucial role in improving the quality of life for cancer patients, particularly those in advanced stages of the disease. Despite its proven benefits, attitudes toward palliative care vary widely among patients due to cultural beliefs, personal values, and awareness of available services. Understanding cancer patients’ perspectives on palliative care is essential for enhancing end-of-life care strategies and ensuring that interventions align with their preferences. However, limited research has explored patients’ attitudes toward palliative care in China, highlighting the need for further investigation.ObjectivesTo explore the current status of cancer patients’ palliative care attitudes, identify subgroups of attitudes and examine influencing factors for different subgroups; and understand the cancer patients’ perceptions of palliative care.MethodsA multi-method design was used. 541 cancer patients participated from March to June 2024. A latent profile analysis (LPA) was conducted to identify subgroups. The differences between the variables including sociodemographic characteristics and subgroups were explored, and participants also responded to open-ended questions about what perceptions on palliative care, and content analysis identified themes most frequently reported.ResultsPalliative care attitudes among cancer patients were low. Four different subgroups of palliative care attitudes and three themes about perspectives were confirmed. Education status, occupational status, primary caregivers, type of insurance, cancer stage, anxiety, and level of palliative care knowledge were significant factors affecting different groups (p < 0.05).ConclusionMajority of cancer patients had poor attitudes toward palliative care, confirming the major factors and perspectives of palliative care. These results emphasize the importance that should be given to the dissemination of knowledge and education about palliative care for cancer patients, and to improve the acceptance and recognition in order to promote palliative care practice.